Vitamins in Cereals: A Critical Review of Content, Health Effects, Processing Losses, Bioaccessibility, Fortification, and Biofortification Strategies for Their Improvement - Garg, Monika; Sharma, Anjali; Vats, Shreya; Tiwari, Vandita; Kumari, Anita; Mishra, Vibhu; Krishania, Meena (Frontiers in Nutrition, 2021)
Cereals are staple food and good sources of A, B and E vitamins. As these are cheapest food and consumed in large quantities, therefore attempts are being made to enrich cereals by fortification and biofortification to address associated deficiency disorders in the venerable population with limited diet diversity. Vitamin content in cereals is significantly affected by their processing/cooking method. Milling can result in substantial reduction depending upon the localization of vitamin in the grain. Method of cooking can have significant impact on retention of vitamins and their bioaccessibility. Minimum cooking losses have been observed for the boiling and highest with pressure cooking. Recommendations have been made for the fortification of cereal flour with specified quantities of frequently deficient vitamins, B1, B2, B3, and B9 along with regional deficiency specific fortification with synthetic and biological sources. Biofortification is the new concept and is being exploited for generation of vitamin rich crops. Biofortified crop once developed, can be utilized for several years. Success story of cereal biofortification includes, provitamin A enriched maize. Wheat grass germinated from wheat seed has also been documented as source of several vitamins (unconfirmed studies).